ADVANCEMENTS IN OPHTHALMIC BIOSIMILARS: A PARADIGM SHIFT IN RETINAL DISEASE MANAGEMENT - Khaqan, Hussain Ahmad; Naz , Raheela; ur Rehman , Hafiz Ateeq; Hassan, Laraib; Akram , Nabeel; Farooqui , Hafiz Mubashir; Fauzan , Ahmad; Mahmood Khan , Asad; Asif, Muhammad Iqbal; Maheshwary, Neeta; et al. (Pakistan Journal of Physiology, 2024)
Diabetes macular oedema (DME) stands as the most prevalent cause of vision impairment. This systematic review aimed to assess clinical studies on the efficacy of top anti-vascular endothelial growth factor (anti-VEGF) agents and their biosimilars in treating diabetic macular œdema. This meta-analysis delves into the transformative impact of biosimilars on retinal disease management in ophthalmology, focusing on the global approval and increasing integration of bevacizumab and adalimumab biosimilars. The bevacizumab biosimilars section explores their approval and cost-effectiveness, particularly in the nuanced application of bevacizumab for retinal diseases. This study highlights the potential utility of biosimilars in treating non-infectious uveitis and discusses economic implications and feasibility in retinal disease management. The profound transformation in retinal disease management, specifically in DME, is underscored, emphasizing the shift from traditional approaches to anti-VEGF therapies, and positive outcomes in visual and anatomical aspects are cited. Addressing a critical need, the abstract emphasizes ongoing research into the long-term efficacy and safety of biosimilars. The importance of guidelines and thorough investigations for sustained positive patient outcomes is highlighted. The continuous quest for innovative therapies to enhance vision outcomes for DME patients is acknowledged. Underscoring the significance of stringent quality control and pharmacovigilance, it emphasizes the need for robust monitoring and immunogenicity testing assays before market approval. The meta-analysis summarizes the monumental shift in retinal disease management due to biosimilar advancements, highlighting their potential for economic solutions and a broader array of treatment options. Pak J Physiol 2024;20(2):70-4